Islamic Boarding Schools' Strategies for Addressing Student Alumni Unemployment (A Study of Islamic Boarding Schools in Greater Malang) - Mujtahid Mujtahid; Ali Hasan Assidiqi; Dini Sadiyah; Zaharah Binti Hussin (Mudir: Jurnal Manajemen Pendidikan, 2026)
Unemployment is a social issue that continues to be a challenge in Indonesia, including in the Greater Malang area. Islamic boarding school graduates often experience difficulties entering the formal workforce due to a lack of technical skills and access to employment. This study aims to examine the educational strategies implemented by Islamic boarding schools to address unemployment among Islamic boarding school students. The method used was a descriptive qualitative approach, with data collection techniques through interviews, observation, and documentation. The research focused on several Islamic boarding schools in Greater Malang that have integrated vocational education, entrepreneurship training, and the use of digital technology into their learning systems. The novelty of this research lies in its focus on the strategies employed Islamic boarding schools and the outcomes observed among their alumni. The results indicate that the most effective strategies include strengthening the vocational curriculum, establishing Islamic boarding school business units, collaborating with training institutions and industry, and instilling a sense of independence and a work ethic. Furthermore, Islamic boarding schools implement strategies based on the integration of religious education, practical skills training (agriculture, carpentry, culinary arts, information technology, handicrafts), Islamic value-based entrepreneurship development, and partnerships with industry and job training institutions. These strategies significantly contribute to reducing the unemployment rate among Islamic boarding school students and encouraging the creation of economically independent students. This study recommends continued support from the government and community to strengthen the role of Islamic boarding schools as agents of economic empowerment for the community.